Management of libraries in 21th century papers presented in the national seminar held at the University of Calicut, 28-29 May, 1999 - Bavakutty, M (Ed.); Paramerwaran, M (Ed.) (New Delhi Ess Ess, 2000)
The conventional library administration has changed to scientific management of libraries and information resourcses. Owing to the development of technology, the information services have increased in their variety, quantity and quality. There is also an
Keywords: Library administration; Management; Information technology